(untitled) (Journal of Comparative Social Work, 2023)
This paper makes a case for Gram Panchayats (or local self-governments) in rural Haryana to prevent violence and abuse against women in cross-regional marriages, and to promote inclusiveness. By using the notion of decentralization as the framework, the results of this research are based on a qualitative fieldwork conducted over two months in the Mahendragarh district, which included visits to seven villages, and interviews with women and village leaders. This paper attempts to answer the following research question: In what ways can strong local self-governments improve the social conditions for women and their children in cross-regional marriages in rural Haryana? Gram Panchayats are tasked with implementing Goal 16 of the Sustainable Development Goals (SDGs), which calls for developing inclusive and peaceful communities, ensuring that everyone has access to justice, and creating effective, inclusive institutions at all levels. The findings reveal that women, particularly those in cross-region marriages, are excluded from participating in Gram Panchayats, which have the potential to be the go-to institution for women in need of help. Women’s participation at all levels will increase the transparency and accountability of Gram Panchayats.